MetDecode: methylation-based deconvolution of cell-free DNA for noninvasive multi-cancer typing - Passemiers, Antoine; Tuveri, Stefania; Sudhakaran, Dhanya; Jatsenko, Tatjana; Laga, Tina; Punie, Kevin; Hatse, Sigrid; Tejpar, Sabine; Coosemans, An; Van Nieuwenhuysen, Els; Timmerman, Dirk; Floris, Giuseppe; et al. (Bioinformatics (Oxford, England), 2024)
MOTIVATION: Circulating-cell free DNA (cfDNA) is widely explored as a noninvasive biomarker for cancer screening and diagnosis. The ability to decode the cells of origin in cfDNA would provide biological insights into pathophysiological mechanisms, aiding in cancer characterization and directing clinical management and follow-up. RESULTS: We developed a DNA methylation signature-based deconvolution algorithm, MetDecode, for cancer tissue origin identification. We built a reference atlas exploiting de novo and published whole-genome methylation sequencing data for colorectal, breast, ovarian, and cervical cancer, and blood-cell-derived entities. MetDecode models the contributors absent in the atlas with methylation patterns learnt on-the-fly from the input cfDNA methylation profiles. In addition, our model accounts for the coverage of each marker region to alleviate potential sources of noise. In-silico experiments showed a limit of detection down to 2.88% of tumor tissue contribution in cfDNA. MetDecode produced Pearson correlation coefficients above 0.95 and outperformed other methods in simulations (P < 0.001; T-test; one-sided). In plasma cfDNA profiles from cancer patients, MetDecode assigned the correct tissue-of-origin in 84.2% of cases. In conclusion, MetDecode can unravel alterations in the cfDNA pool components by accurately estimating the contribution of multiple tissues, while supplied with an imperfect reference atlas. AVAILABILITY AND IMPLEMENTATION: MetDecode is available at https://github.com/JorisVermeeschLab/MetDecode.
Keywords: Biomarkers, Tumor; algoritmy; nádory; nádorové biomarkery; DNA Methylation; metylace DNA; Humans; lidé; Algorithms; Cell-Free Nucleic Acids; volné cirkulující nukleové kyseliny; Neoplasms